Adsorption desulfurization catalyst and its preparation method and application

By using an adsorption desulfurization catalyst prepared with a specific carrier and metal components in the desulfurization treatment of heavy oil, the problem of poor desulfurization effect of heavy oil in the existing technology is solved, and efficient and stable desulfurization effect is achieved.

CN116408099BActive Publication Date: 2025-01-21PETROCHINA CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202111646145.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-01-21
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

The existing desulfurizers have limited effects in the desulfurization treatment of heavy oils, and their strength, desulfurization activity and stability need to be further improved.

Method used

It uses a carrier compounded of macroporous pseudo-boehmite, small-pore pseudo-boehmite and titanium oxide, combined with metal components such as zinc, nickel, molybdenum and/or tin, and is prepared through multi-step impregnation and reduction treatments. Efficient adsorption desulfurization catalyst.

Benefits of technology

The desulfurization rate is significantly improved, the catalyst has high strength and good stability, is suitable for deep desulfurization of heavy oil, and has good mechanical properties and long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003443925030000201
    Figure BDA0003443925030000201
  • Figure HDA0003443925040000011
    Figure HDA0003443925040000011
  • Figure HDA0003443925040000021
    Figure HDA0003443925040000021
Patent Text Reader

Abstract

The present invention provides an adsorption desulfurization catalyst and a preparation method and application thereof, wherein the adsorption desulfurization catalyst comprises a carrier, a first metal component and a second metal component, wherein the first metal component comprises zinc and nickel, and the second metal component comprises molybdenum and / or tin, and the carrier is compounded from raw materials comprising macroporous pseudo-boehmite, microporous pseudo-boehmite and titanium oxide, wherein the pore volume of the macroporous pseudo-boehmite is not less than 0.8 mL / g, and the pore volume of the microporous pseudo-boehmite is not more than 0.8 mL / g. The adsorption desulfurization catalyst of the present invention has the advantages of high strength, good stability and high desulfurization efficiency, and is particularly suitable for desulfurization treatment of heavy oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adsorption desulfurization catalyst and a preparation method and application thereof, belonging to the field of desulfurization of sulfur-containing oil products. Background Art

[0002] With the improvement of environmental protection requirements, low-sulfur clean oil products have gradually become the focus of attention. Taking marine fuel oil as an example, its combustion process will produce pollutants such as sulfides. In order to control pollution, the International Maritime Organization (IMO) announced that it will enforce new sulfur emission restrictions from January 1, 2020. Therefore, it is urgent to reduce the sulfur content in fuel oil and other oil products and develop low-sulfur clean oil products. In addition, desulfurization of heavy oil such as residual oil and converting it into low-sulfur clean oil products as a blending component of fuel oil and other oil products is an important way to achieve efficient utilization of heavy oil.

[0003] Hydrodesulfurization and adsorption desulfurization are common means to achieve the purpose of oil desulfurization, for example, patent document CN101439288A discloses a combined alumina-based selective hydrodesulfurization catalyst and a preparation method thereof, which are used for the selective hydrodesulfurization of gasoline; CN112742370A discloses a catalyst composition and its application and a method for selective desulfurization of mercaptans, which are used to remove mercaptans from oil products; CN106824068A discloses a bamboo-derived porous biomass fuel oil highly selective adsorption desulfurizer, which is prepared by chemical activation carbonization and concentrated nitric acid oxidation, and is used for the selective adsorption desulfurization of fuel oil; CN101439288A discloses an adsorption desulfurization catalyst for removing sulfur from cracked gasoline; CN102463099A discloses an adsorption A desulfurization adsorbent and a preparation method thereof are used for desulfurization treatment of cracked gasoline and diesel, thereby increasing the octane number of cracked gasoline and improving the low-temperature flow properties of diesel; CN103372416A discloses an adsorbent for hydrocarbon oil desulfurization and a preparation method thereof, wherein the adsorbent is used for adsorption desulfurization of gasoline to increase the octane number of gasoline; CN104056632A discloses a fuel oil deep adsorption desulfurization catalyst and a preparation method and application thereof, which has a good desulfurization effect on catalytic cracking gasoline; CN104028217A discloses a gasoline highly selective adsorption desulfurizer, which is composed of nickel oxide, zinc oxide and carbon aerogel and is used for the selective desulfurization of gasoline; CN104511285A discloses a desulfurization catalyst, which is used for desulfurization treatment of cracked gasoline and diesel engine fuel.

[0004] Desulfurizer is an important factor affecting the desulfurization effect. Optimizing the structure and performance of desulfurizer is an effective means to improve the desulfurization effect. Although there have been studies and reports on desulfurizers such as hydrodesulfurizers and adsorption desulfurizers, on the one hand, the strength, desulfurization activity, stability and desulfurization efficiency of desulfurizers at this stage need to be further improved. On the other hand, the current desulfurizers are mostly used for the desulfurization of light oils such as gasoline, kerosene and diesel, but have limited desulfurization effects on heavy oils. It is urgent to develop effective desulfurizers suitable for the desulfurization of heavy oils. Summary of the invention

[0005] The present invention provides an adsorption desulfurization catalyst and a preparation method and application thereof, which has the advantages of high catalyst strength, good stability and high desulfurization efficiency, and is particularly suitable for desulfurization treatment of heavy oil, effectively overcoming the defects of the prior art.

[0006] In one aspect of the present invention, there is provided an adsorptive desulfurization catalyst, comprising a carrier, a first metal component and a second metal component, wherein the first metal component comprises zinc and nickel, the second metal component comprises molybdenum and / or tin, and the carrier is compounded from raw materials comprising macroporous pseudo-boehmite, microporous pseudo-boehmite and titanium oxide, wherein the pore volume of the macroporous pseudo-boehmite is not less than 0.8 mL / g, and the pore volume of the microporous pseudo-boehmite is not more than 0.8 mL / g.

[0007] According to one embodiment of the present invention, based on the oxide of the first metal component and the oxide of the second metal component, the following conditions are met: the mass of the first metal component accounts for 50% to 80% of the sum of the masses of the carrier and the first metal component; and / or the mass of nickel in the first metal component accounts for 3% to 15% of the sum of the masses of the carrier and the first metal component; and / or the mass of the second metal component accounts for 0.5% to 2% of the sum of the masses of the carrier and the first metal component.

[0008] According to one embodiment of the present invention, the pore volume of the small-pore pseudo-boehmite is 0.4 mL / g to 0.8 mL / g, and the specific surface area is 180 m 2 / g~260m 2 / g, the peptization index is greater than 95%; and / or the pore volume of the macroporous pseudo-boehmite is 0.8mL / g to 1.2mL / g, the specific surface area is 260m 2 / g~360m 2 / g; and / or, the mass ratio of the small-pore pseudo-boehmite to the large-pore pseudo-boehmite is 1:(2.5-4.5); and / or, the ratio of the mass of the titanium oxide to the sum of the masses of the large-pore pseudo-boehmite and the small-pore pseudo-boehmite is (0.1-0.3):1.

[0009] In another aspect of the present invention, a method for preparing the above-mentioned adsorptive desulfurization catalyst is provided, comprising: (I) adding an inorganic acid and water to a mixture containing macroporous pseudo-boehmite, microporous pseudo-boehmite, titanium oxide, a binder, and zinc oxide, and then sequentially performing molding, drying, and calcining to obtain a first intermediate; (II) impregnating the first intermediate with a first impregnation solution containing a nickel compound, and drying and calcining the impregnation product to obtain a second intermediate; (III) impregnating the second intermediate with a second impregnation solution containing a compound of a second metal component, and drying and calcining the impregnation product to obtain a catalyst precursor; and (IV) performing a first reduction treatment on the catalyst precursor in an atmosphere containing hydrogen to obtain the adsorptive desulfurization catalyst.

[0010] According to one embodiment of the present invention, the zinc oxide comprises nano zinc oxide powder with a particle size not greater than 100 nm; and / or the binder comprises at least one of sodium methyl cellulose, sodium carboxymethyl starch, sodium carboxymethyl cellulose, and sesbania powder; and / or the nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 1% to 5% of the sum of the masses of the macroporous pseudo-boehmite, microporous pseudo-boehmite, titanium oxide, zinc oxide and nickel compound; and / or the ratio of the mass of the inorganic acid to the sum of the masses of the macroporous pseudo-boehmite and microporous pseudo-boehmite is (0.1 to 0.5):1.

[0011] According to one embodiment of the present invention, the calcination conditions in step (I) are: the calcination temperature is 400°C to 700°C, and the calcination time is 1h to 10h; and / or, the calcination conditions in step (II) are: the calcination temperature is 400°C to 700°C, and the calcination time is 1h to 10h; and / or, the calcination conditions in step (III) are: the calcination temperature is 400°C to 700°C, and the calcination time is 1h to 10h; and / or, in step (IV), the volume space velocity of hydrogen is 500h-10 -1 ~4000h -1 The temperature of the first reduction treatment process is 300°C to 500°C, the pressure of the first reduction treatment process is 0 to 3MPa, and the time of the first reduction treatment is 1h to 6h.

[0012] In another aspect of the present invention, a method for desulfurization of sulfur-containing oil is provided, comprising: using the above-mentioned adsorption desulfurization catalyst to desulfurize the sulfur-containing oil; or, preparing the adsorption desulfurization catalyst according to the above-mentioned preparation method, and using the prepared adsorption desulfurization catalyst to desulfurize the sulfur-containing oil.

[0013] According to one embodiment of the present invention, the temperature of the desulfurization treatment is 300°C to 550°C; and / or, the pressure of the desulfurization treatment is 0.5MPa to 10MPa; and / or, the feed space velocity of the sulfur-containing oil product is 0.1h-1 ~1.0h -1 ; and / or, the desulfurization treatment is carried out under a hydrogen atmosphere, and the volume ratio of the hydrogen to the sulfur-containing oil is (100-800):1.

[0014] According to one embodiment of the present invention, the method further comprises: obtaining a desulfurized oil product and a regenerated catalyst after the desulfurization treatment; regenerating the regenerated catalyst to obtain a regenerated catalyst; and returning the regenerated catalyst to the desulfurization treatment; wherein the regeneration treatment comprises: subjecting the regenerated catalyst to oxidation regeneration in the presence of an oxygen-containing gas to obtain a regenerated catalyst precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, and the volume space velocity of the oxygen-containing gas is 1000 h / min. -1 ~3000h -1 The temperature of the oxidation regeneration is 300°C to 500°C, the pressure of the oxidation regeneration is 0 to 0.5 MPa, and the time of the oxidation regeneration is 20h to 100h; the regenerated catalyst precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain the regenerated catalyst; wherein the volume space velocity of the hydrogen is 500h -1 ~4000h -1 The temperature of the second reduction treatment is 300° C. to 500° C., the pressure of the second reduction treatment is 0 to 3 MPa, and the time of the second reduction treatment is 1 h to 6 h.

[0015] According to one embodiment of the present invention, the sulfur component in the sulfur-containing oil product includes at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, and the thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene; and / or, the sulfur-containing oil product includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

[0016] The adsorption desulfurization catalyst provided by the present invention has the advantages of good mechanical properties, long service life, good desulfurization activity, etc., can significantly improve the desulfurization rate, and has a wide range of applications, especially suitable for the desulfurization treatment of heavy oil, effectively removes sulfides such as thiophenes, realizes the deep desulfurization of sulfur-containing oil products such as heavy oil, improves the quality of the desulfurized oil products, and the desulfurized oil products can be used as clean gasoline blending components or other purposes. Studies have shown that the fracture strength of the adsorption desulfurization catalyst is as high as 30N or more, showing good mechanical properties, good structural stability, meeting the requirements of processes such as moving beds, and having a wide range of applications; the desulfurization rate of heavy oil is as high as 75% or more, and the adsorption desulfurization catalyst can still achieve a good desulfurization rate after being regenerated 1 to 35 times or even higher times, showing good activity stability and long service life. In addition, the raw materials of the adsorption desulfurization catalyst of the present invention are cheap and easy to obtain, and it also has the advantages of low cost, simple preparation process, and simple desulfurization process using the adsorption desulfurization catalyst, mild conditions, and high efficiency, which is of great significance for practical industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 XRD spectra of catalyst precursors during the preparation of fresh adsorption desulfurization catalysts S1, S2, D3, and D4 (the abscissa is the 2θ angle (Theta), and the ordinate is the peak intensity (intensity));

[0018] Figure 2 This is the XRD spectrum of the regenerated catalyst precursor during the regeneration process of the spent catalyst produced after desulfurization treatment of S1, S2, D3, and D4. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only descriptions of the principles and features of the present invention. The examples given are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In the description of the present invention, terms such as "first" and "second" are only used for descriptive purposes, such as distinguishing between components to more clearly illustrate / explain the technical solution, and cannot be understood as indicating or implying the number of technical features indicated or the order of substantial significance.

[0020] The adsorption desulfurization catalyst of the present invention includes a carrier, a first metal component and a second metal component, the first metal component includes zinc and nickel, the second metal component includes molybdenum and / or tin, and the carrier is compounded by raw materials including macroporous pseudo-boehmite, microporous pseudo-boehmite and titanium oxide, wherein the pore volume of the macroporous pseudo-boehmite is not less than 0.8 mL / g, and the pore volume of the microporous pseudo-boehmite is not more than 0.8 mL / g.

[0021] After research and analysis, the inventor believes that, in the adsorption desulfurization catalyst composition system of the present invention, the first metal component serves as the main active component for sulfur adsorption / absorption. During the desulfurization treatment of the oil product, the sulfur element in the oil product is captured by the nickel component in the catalyst to form nickel sulfide. The nickel sulfide reacts with the zinc component to form zinc sulfide. The second metal component, as an active metal, can promote the sulfur transfer and other processes. Thus, through multi-step coordinated reactions, the sulfur component in the oil product is adsorbed in the adsorption desulfurization catalyst in the form of metal sulfides such as zinc sulfide, thereby achieving the purpose of desulfurization.

[0022] Generally speaking, when using conventional alumina-based carriers and adsorption desulfurization catalysts with zinc oxide and nickel as the main adsorption active components for adsorption desulfurization of heavy oil, there will be at least the following problems: First, due to the inherent properties of ZnO as the main adsorption component, the strength of the catalyst is poor; second, there is a strong interaction between the adsorption active components (such as ZnO) and the carrier Al2O3, and zinc-aluminum spinel is easily formed during the adsorption desulfurization reaction, catalyst regeneration and other cyclic processes, causing some adsorption active components such as ZnO to lose the ability to desulfurize and store sulfur, thereby gradually deactivating the catalyst. At the same time, it will also reduce the strength of the catalyst, affecting the desulfurization performance and service life of the catalyst.

[0023] According to the research of the present invention, the above-mentioned problem can be effectively solved by using the carrier composed of large-pore pseudo-boehmite, small-pore pseudo-boehmite and titanium oxide, matching the above-mentioned first metal component and the second metal component, forming an adsorption desulfurization catalyst. The inventor believes through research and analysis that the carrier is formed by compounding small-pore pseudo-boehmite, large-pore pseudo-boehmite and titanium oxide, so that there is a double aluminum structure in the catalyst, combined with matching titanium oxide, the strength and other properties of the catalyst can be significantly improved. Among them, the large-pore pseudo-boehmite has the characteristics of large pore volume and specific surface area, which can improve the dispersion of active components such as zinc oxide, and at the same time facilitate the diffusion of sulfides into the catalyst during the desulfurization process, thereby improving the contact efficiency between the catalyst and the sulfide and improving the desulfurization activity. The introduction of titanium oxide can further ensure the improvement of the dispersion of active components in the catalyst, weaken the interaction between aluminum oxide and zinc oxide, and inhibit the formation of zinc-aluminum spinel, thereby ensuring the strength, desulfurization activity and stability of the catalyst, facilitating its recycling and regeneration and improving its service life.

[0024] To further optimize the catalyst performance, the pore volume of the small-pore pseudo-boehmite can be 0.4 mL / g to 0.8 mL / g, such as 0.4 mL / g, 0.5 mL / g, 0.6 mL / g, 0.7 mL / g, 0.8 mL / g or any two thereof, and the specific surface area is 180 m 2 / g~260m 2 / g, for example 180m2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g or any two thereof, and its peptization index is greater than 95%.

[0025] In addition, the pore volume of the macroporous pseudo-boehmite can be 0.8 mL / g to 1.2 mL / g, such as 0.8 mL / g, 0.9 mL / g, 1.0 mL / g, 1.1 mL / g, 1.2 mL / g or any two thereof, and the specific surface area is 260 m 2 / g~360m 2 / g, for example 260m 2 / g, 270m 2 / g, 280m 2 / g, 290m 2 / g、300m 2 / g, 310m 2 / g, 320m 2 / g, 330m 2 / g, 340m 2 / g, 350m 2 / g, 360m 2 / g or a range consisting of any two thereof.

[0026] In some embodiments, the mass ratio of small-pore pseudo-boehmite to large-pore pseudo-boehmite may be 1:(2.5-4.5), such as 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or a range consisting of any two of them.

[0027] In some embodiments, the ratio of the mass of titanium oxide to the sum of the mass of large-pore pseudo-boehmite and small-pore pseudo-boehmite is (0.1-0.3):1, for example, 0.1:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1 or a range consisting of any two of them.

[0028] In the above-mentioned adsorption desulfurization catalyst, the mass percentage of the first metal component serving as the sulfur absorption unit is generally not lower than (i.e., equal to or greater than) the mass percentage of the carrier. In some preferred embodiments, the mass of the first metal component, calculated as the oxide of the first metal component, accounts for 50% to 80% of the sum of the masses of the carrier and the first metal component, for example, 50%, 55%, 60%, 65%, 70%, 80% or the range consisting of any two thereof, and the mass of the carrier accounts for 20% to 50% of the sum of the masses of the carrier and the first metal component, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50% or the range consisting of any two thereof.

[0029] In general, the mass percentage of zinc in the first metal component is preferably higher than the mass percentage of nickel, calculated as the oxide of the first metal component. In some embodiments, the mass of nickel in the first metal component accounts for 3% to 15% of the sum of the mass of the support and the first metal component, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or a range consisting of any two thereof, calculated as the oxide of the first metal component.

[0030] In some embodiments, the mass of the second metal component, calculated as the oxide of the first metal component and the oxide of the second metal component, accounts for 0.5% to 2% of the sum of the masses of the support and the first metal component, for example, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2% or a range consisting of any two thereof.

[0031] In the above-mentioned adsorptive desulfurization catalyst, the first metal component and the second metal component are loaded on a carrier. Generally, most of the metal components exist in the form of oxides (such as zinc exists in the form of zinc oxide), wherein at least part of the nickel can be present in a reduced state (i.e., in the form of nickel element). In specific implementation, compounds of each metal component can be used to load each metal component on a carrier by an impregnation method. After the loading of each metal component is completed, the obtained catalyst precursor is subjected to a first reduction treatment in an atmosphere containing hydrogen, so that the nickel component therein is at least partially reduced to nickel element, thereby obtaining an adsorptive desulfurization catalyst and improving its desulfurization activity.

[0032] The above-mentioned carrier can be specifically prepared by compounding raw materials containing macroporous pseudo-boehmite, microporous pseudo-boehmite, titanium oxide and a binder, and its preparation process can include: mixing macroporous pseudo-boehmite, microporous pseudo-boehmite, titanium oxide, a binder with an inorganic acid and water, and then drying and calcining to form a carrier. The metal component can be introduced during the preparation of the carrier, or the metal component can be impregnated after the carrier is prepared.

[0033] In a preferred embodiment of the present invention, the preparation method of the above-mentioned adsorptive desulfurization catalyst comprises: (I) adding inorganic acid and water to a mixture containing macroporous pseudo-boehmite, microporous pseudo-boehmite, titanium oxide, a binder, and zinc oxide, and then sequentially performing molding, drying, and calcining to obtain a first intermediate; (II) impregnating the first intermediate with a first impregnation solution containing a nickel compound, and drying and calcining the impregnation product to obtain a second intermediate; (III) impregnating the second intermediate with a second impregnation solution containing a compound of a second metal component, and drying and calcining the impregnation product to obtain a catalyst precursor; (IV) performing a first reduction treatment on the catalyst precursor in an atmosphere containing hydrogen to obtain an adsorptive desulfurization catalyst.

[0034] In the above preparation process, zinc oxide is first mixed with carrier raw materials (macroporous pseudo-boehmite, microporous pseudo-boehmite, titanium oxide, and binder) to form a mixture, and then nickel compounds and second metal components are sequentially impregnated to improve the strength and desulfurization activity of the prepared adsorption desulfurization catalyst. The inventor believes through research and analysis that in the above preparation process, after drying and calcination in steps (I) to (III), macroporous pseudo-boehmite, microporous pseudo-boehmite, and titanium oxide are compounded to form a carrier, and the binder gradually volatilizes during the calcination process, thereby forming a pore structure in the prepared catalyst, and the nickel compound and the compound of the second metal component are basically converted into metal oxides; after the first reduction treatment in step (IV), the nickel therein can be basically present in a reduced state, while other metal components (such as zinc and the second metal component) are usually still present in the form of metal oxides, thereby preparing an adsorption desulfurization catalyst with suitable composition and structure, which is suitable for desulfurization of heavy oil, and can show good adsorption desulfurization activity, stability, mechanical properties and other characteristics, and improve desulfurization rate and service life.

[0035] Specifically, in the above preparation process, the first metal component compound includes zinc oxide and nickel compound, and the second metal component compound includes molybdenum compound and / or tin compound. In general, the content of each metal component in the obtained adsorption desulfurization catalyst can be regulated by the amount of raw materials such as each metal component compound, and the amount of each raw material is as follows: based on the oxide of each metal component (such as nickel compound based on nickel oxide, molybdenum compound based on molybdenum oxide, and tin compound based on tin oxide), the mass of the first metal component compound accounts for 50% to 80% of the sum of the mass of the carrier and the first metal component compound, the mass of the nickel compound accounts for 3% to 15% of the sum of the mass of the carrier and the first metal component compound, the mass of the second metal component compound accounts for 0.5% to 2% of the sum of the mass of the carrier and the first metal component compound, the mass ratio of small-pore pseudo-boehmite to large-pore pseudo-boehmite is 1: (2.5 to 4.5), and the mass ratio of titanium oxide to the sum of the mass of large-pore pseudo-boehmite and small-pore pseudo-boehmite is (0.1 to 0.3): 1.

[0036] In step (I), the mixture can be a wet mixture, a paste mixture, a kneaded body or a slurry, etc., and the molding process can be oil-ammonia column molding, oil-water column molding, oil column molding, rolling ball molding or extrusion ball molding, etc., preferably extrusion ball molding, wherein the amount of water used can be convenient for molding, for example, it can meet the extrusion ball molding, and there is no particular restriction on this. Through the above molding process, the first intermediate formed can be spherical and / or toothed ball-shaped, and the particle diameter of the first intermediate is preferably 1.5mm to 3mm, for example, 1.5mm, 2mm, 2.5mm, 3mm or the range composed of any two thereof.

[0037] In step (I), the zinc oxide may include nano-sized particles of zinc oxide, preferably nano zinc oxide powder with a particle size of no more than 100 nm. In specific implementation, the purity of the zinc oxide used is greater than 96%.

[0038] In step (I), the binder may include at least one of sodium methyl cellulose, sodium carboxymethyl starch, sodium carboxymethyl cellulose, and sesbania powder. In addition, the amount of the binder can generally be controlled as follows: the mass of the nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 1% to 5% of the sum of the mass of macroporous pseudo-boehmite, microporous pseudo-boehmite, titanium oxide, zinc oxide and the nickel compound, for example, 1%, 2%, 3%, 4%, 5% or a range consisting of any two of them.

[0039] In some embodiments, in step (I), the ratio of the mass of the inorganic acid to the sum of the mass of the macroporous pseudo-boehmite and the microporous pseudo-boehmite is (0.1-0.5):1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1 or any two of them. It should be noted that the ratio of the mass of the inorganic acid to the sum of the mass of the macroporous pseudo-boehmite and the microporous pseudo-boehmite is calculated based on the inorganic acid without solvents such as water. In specific implementation, inorganic acid solutions of different concentrations may be used, and the mass of the inorganic acid therein can be converted according to its concentration, and the ratio of the mass of the inorganic acid (non-solution) to the sum of the mass of the macroporous pseudo-boehmite and the microporous pseudo-boehmite is controlled to be (0.1-0.5):1. Preferably, the inorganic acid comprises nitric acid.

[0040] In step (II), the first impregnation solution may be a solution or a suspension, and the nickel compound may include a soluble nickel compound (generally a water-soluble nickel compound) in particular. The first impregnation solution is a solution prepared by dissolving the soluble nickel compound in water. The soluble nickel compound includes, for example, a soluble nickel salt, preferably nickel nitrate and / or nickel acetate. The soluble nickel salt may be in the form of a hydrate without or with water of crystallization, and the present invention is not particularly limited to this.

[0041] In specific implementation, in step (II), the impregnation can be performed by an equal volume impregnation method. In some embodiments, in step (II), the impregnation temperature is 20°C to 90°C, such as 20°C, 30°C, 40°C, 50°C, 60°C, 65°C, 70°C, 80°C, 90°C or any two thereof, and the impregnation time is 1h to 24h, such as 1h, 5h, 10h, 15h, 20h, 24h or any two thereof.

[0042] In step (III), the second impregnation liquid can be a solution or a suspension, which can be specifically prepared by mixing a compound of the second metal component with water, and the compound of the second metal component can include ammonium molybdate and / or stannous chloride. In specific implementation, in step (III), the impregnation can be carried out by an equal volume impregnation method. In some embodiments, in step (III), the impregnation temperature is 20°C to 90°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 65°C, 70°C, 80°C, 90°C or any two thereof, and the impregnation time is 1h to 24h, for example, 1h, 5h, 10h, 15h, 20h, 24h or any two thereof; the mass ratio of the second impregnation liquid to the second intermediate is (1.5 to 3.5): 1, for example, 1: 1, 2: 1, 1.5: 1, 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1 or any two thereof.

[0043] Optionally, the drying process in step (I), step (II) and step (III) independently comprises: first drying at 20°C to 30°C (such as room temperature) for 12h to 48h, then drying at 60°C to 120°C (preferably 80°C to 110°C) for 3h to 24h, preferably 6h to 10h, and then calcining the obtained dried product. The drying temperature, drying time and other conditions in step (I), step (II) and step (III) may be the same or different.

[0044] In addition, the calcination conditions in step (I), step (II), and step (III) can be independently: the calcination temperature is 400°C to 700°C, such as 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, or a range consisting of any two thereof, preferably 450°C to 650°C, and the calcination time is 1h to 10h, such as 1h, 3h, 5h, 7h, 10h, or a range consisting of any two thereof, preferably 3h to 5h. Among them, the calcination temperature, calcination time, etc. in step (I), step (II), and step (III) can be the same or different.

[0045] In step (IV), hydrogen can be introduced into the system to contact the catalyst precursor with hydrogen to perform the first reduction treatment. The volume space velocity of hydrogen can be 500h -1 ~4000h -1 , for example 500h -1 、1000h -1 、1500h -1 , 2000h -1 、2500h -1 、3000h -1 、3500h -1 , 4000h -1 Or any two of them, preferably 1500h -1 ~3000h -1 Generally, in step (IV), the volume fraction of hydrogen in the atmosphere containing hydrogen is 50% to 100%, such as 50%, 60%, 70%, 80%, 90%, 100% or any two thereof, and the remainder is, for example, an inert gas.

[0046] In step (IV), the temperature of the first reduction treatment process can be 300°C to 500°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two thereof, the pressure of the first reduction treatment process is 0 to 3MPa, for example, 0MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa or a range consisting of any two thereof, preferably 0.5 to 1.5MPa, and the time of the first reduction treatment is 1h to 6h, for example, 1h, 2h, 3h, 4h, 5h, 6h or a range consisting of any two thereof, preferably 2h to 4h.

[0047] In the present invention, unless otherwise specified, the masses of macroporous pseudo-boehmite and microporous pseudo-boehmite are calculated on a dry basis of alumina, and the masses of raw materials such as titanium oxide and zinc oxide are also calculated on a dry basis.

[0048] In one embodiment of the present invention, a method for desulfurization of sulfur-containing oil products is provided, comprising: using the above-mentioned adsorption desulfurization catalyst to desulfurize the sulfur-containing oil products; or, preparing the adsorption desulfurization catalyst according to the above-mentioned preparation method, and using the prepared adsorption desulfurization catalyst to desulfurize the sulfur-containing oil products.

[0049] In some embodiments, the temperature of the desulfurization treatment can be 300°C to 550°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or a range consisting of any two thereof, preferably 400-450°C; the pressure of the desulfurization treatment is 0.5MPa to 10MPa, for example, 0.5MPa, 1MPa, 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa or a range consisting of any two thereof, preferably 3MPa to 7MPa; the feed space velocity of the sulfur-containing oil is 0.1h -1 ~1.0h -1 , for example 0.1h -1 、0.3h -1 、0.5h -1 、0.8h -1 , 1h -1 Or a range consisting of any two of them.

[0050] In some embodiments, the desulfurization treatment is carried out in a hydrogen atmosphere, that is, the sulfur-containing oil and the adsorption desulfurization catalyst are contacted and reacted in a hydrogen atmosphere to carry out the desulfurization treatment. The volume ratio of hydrogen to the sulfur-containing oil (hydrogen-to-oil volume ratio) is (100-800):1, for example, 100:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, 800:1 or a range consisting of any two of them.

[0051] In some embodiments, the above desulfurization process further includes: obtaining a desulfurized oil product and a regenerated catalyst after desulfurization treatment; regenerating the regenerated catalyst to obtain a regenerated catalyst; and returning the regenerated catalyst for desulfurization treatment.

[0052] The regeneration treatment comprises: subjecting the catalyst to be regenerated to oxidation regeneration in the presence of an oxygen-containing gas to obtain a regenerated catalyst precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two thereof, and the volume space velocity of the oxygen-containing gas is 1000h -1 ~3000h -1 , for example 1000h -1 、1300h -1 、1500h -1 , 1800h -1 , 2000h -1 , 2300h -1 、2500h -1 、2800h -1 、3000h -1or a range consisting of any two thereof; the temperature of the oxidative regeneration is 300°C to 500°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two thereof; the pressure of the oxidative regeneration is 0 to 0.5 MPa; the time of the oxidative regeneration is 20h to 100h; the regenerated catalyst precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain a regenerated catalyst; wherein the temperature of the second reduction treatment ... 0℃, 450℃, 500℃ or any two of them in the range, preferably 350~450℃, the pressure of the second reduction treatment is 0~3MPa, for example 0MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa or any two of them in the range, preferably 0.5~1.5MPa, the time of the second reduction treatment is 1h~6h, for example 1h, 2h, 3h, 4h, 5h, 6h or any two of them in the range, preferably 2h~4h. In the present invention, unless otherwise specified, the pressures are all gauge pressures.

[0053] In a specific implementation, hydrogen can be introduced into the system to contact the regenerated catalyst precursor with hydrogen to perform the second reduction treatment. The volume space velocity of hydrogen can be 500 h -1 ~4000h -1 , for example 500h -1 、1000h -1 、1500h -1 , 2000h -1 、2500h -1 、3000h -1 、3500h -1 , 4000h -1 Or any two of them, preferably 1500h -1 ~3000h -1 Generally, during the second reduction treatment, the volume fraction of hydrogen in the hydrogen-containing atmosphere is 10% to 100%, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% or any two thereof, preferably 60% to 100%, and the remainder may be an inert gas or oil gas such as methane.

[0054] Specifically, the above desulfurization treatment is carried out in a reactor, and the reactor may include a fixed bed reactor and / or a moving bed reactor. Taking the fixed bed reactor as an example, in specific implementation, the adsorption desulfurization catalyst may be loaded in the fixed bed reactor, and then the sulfur-containing oil product enters the fixed bed reactor, and contacts and reacts with the adsorption desulfurization catalyst therein to obtain the desulfurized oil product and the regenerated catalyst respectively; after the regenerated catalyst is subjected to the above regeneration treatment, it is returned to the fixed bed reactor to form a cycle.

[0055] In the present invention, the above-mentioned adsorption desulfurization catalyst is used to remove small molecular sulfides and large molecular sulfides in sulfur-containing oil products, and has a wide range of applications. Generally, the sulfides in the above-mentioned sulfur-containing oil products include at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, but are not limited thereto. Exemplarily, thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene. The present invention can efficiently remove these sulfides in sulfur-containing oil products, especially large molecular sulfides such as thiophenes, thereby achieving deep desulfurization of sulfur-containing oil products and reducing the total sulfur content of the desulfurized oil products.

[0056] Generally speaking, the equivalent double bond value (DBE) of sulfides in heavy oil is distributed between 9 and 16. 22 -C 46 , mainly benzothiophene, dibenzothiophene, benzonaphthothiophene and other macromolecular sulfides, which are difficult to remove, and the asphaltene and colloid particles in the heavy oil are large, which are easy to block the catalyst pores, causing problems such as catalyst deactivation. The adsorption desulfurization catalyst of the present invention can efficiently remove sulfides in heavy oil, and has good activity and stability, can be regenerated and used multiple times, and maintains good desulfurization efficiency. In some specific embodiments, the above-mentioned sulfur-containing oil includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

[0057] In the present invention, the above-mentioned adsorption desulfurization catalyst is used to desulfurize sulfur-containing oil products, and efficient desulfurization can also be achieved for sulfur-containing oil products with high sulfur content (such as the above-mentioned heavy oil). Taking heavy oil with a sulfur content of about 1.7wt% (such as vacuum residue) as an example, through the above-mentioned desulfurization process, the desulfurization rate can reach more than 75%.

[0058] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] In the following embodiments, the relevant performance testing process is as follows:

[0060] (1) With reference to the standard "SH / T 0689-2000", the total sulfur content in the liquid oil sample was determined by ultraviolet fluorescence / chemiluminescence method using the American photonLAB total sulfur and total nitrogen analyzer at a temperature of 1000°C, argon gas of 30psi, and oxygen of 10psi. According to this method, the mass percentage of total sulfur in the heavy oil feedstock x0 and the mass percentage of total sulfur in the desulfurized oil product x1 were determined respectively, and the desulfurization rate w was calculated according to w=(x0-x1) / x0;

[0061] (2) A universal automatic strength tester is used to measure the mechanical strength of the molded particles (such as S1 to S6, D1 to D6 below). The instrument range is 0 to 500 N, and the accuracy is 0.1 N. The measurement process is as follows: a single sample is placed between two rigid platforms, one of which remains stationary and the other moves axially downward at a very low speed to produce extrusion friction on the particles. The fracture strength (or crushing strength) is determined as the maximum load measured before the particles break. According to this process, 50 regular particles are selected for each sample to perform a crushing strength test, so as to obtain representative mechanical properties.

[0062] (3) The crystal structure of each catalyst sample was characterized by X-ray diffraction (XRD) analysis. Specifically, the XRD analysis was performed using a Rigaku D / max 2200PC X-ray powder diffractometer with a Cu target, a graphite monochromator, a scanning speed of 10 degrees / min, a scanning step of 0.02 degrees, a voltage of 40 kV, and a current of 20 mA. The intensity and position of the diffraction peaks in the measured XRD spectrum were used to perform a qualitative analysis to determine the catalyst composition (including the type of substance, structure, crystalline state, and state of element existence, etc.).

[0063] In the following examples and comparative examples, small-pore pseudo-boehmite was purchased from Zibo Yinghe Chemical Co., Ltd., model number YH-2, and the pore volume of the small-pore pseudo-boehmite was 0.55 mL / g and the specific surface area was 227 m 2 / g, the peptization index is greater than 95%; the macroporous pseudo-boehmite was purchased from Zibo Jiarun Chemical Co., Ltd., model JR-G-03, the pore volume of the macroporous pseudo-boehmite raw material is 1.14mL / g, and the specific surface area is 348m 2 / g; other reagents were purchased from Aladdin Reagent Network; the zinc oxide used was nano zinc oxide powder with a particle size of no more than 100 nm. In the following examples and comparative examples, unless otherwise specified, the mass of macroporous pseudo-boehmite and microporous pseudo-boehmite is calculated on a dry basis of aluminum oxide, and the mass of raw materials such as titanium oxide, zinc oxide, and stannous chloride is also calculated on a dry basis.

[0064] Example 1

[0065] (1) 51 g of small-pore pseudo-boehmite, 130 g of large-pore pseudo-boehmite, 19 g of titanium oxide, 50 g of sodium carboxymethyl cellulose and 650 g of zinc oxide powder were mixed uniformly, 400 g of water and 90 g of nitric acid were added, and after mixing uniformly, the mixture was extruded into small balls with a particle diameter of 2 mm, and the small balls were naturally dried at room temperature for 24 hours, then dried at 100° C. for 8 hours, and then calcined at 550° C. for 4 hours to obtain a first spherical intermediate;

[0066] (2) Weighing 584 g of nickel nitrate hexahydrate, adding 1000 g of water to prepare a first impregnation solution, placing the first intermediate in the first impregnation solution, and impregnating at 50° C. for 8 h; drying the obtained impregnation product at room temperature for 24 h, then drying at 80° C. for 10 h, and then calcining at 500° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0067] (3) Weighing 6.8 g of ammonium molybdate, adding 1500 g of water to prepare a second impregnation solution, placing the second intermediate in the second impregnation solution, and impregnating at 60° C. for 6 h; drying the obtained impregnation product at room temperature for 12 h, then drying at 110° C. for 6 h, and then calcining at 600° C. for 3 h to obtain a spherical catalyst precursor;

[0068] (4) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S1; wherein the reduction treatment conditions are: pressure 1 MPa, temperature 400°C, reduction treatment time 3 h, hydrogen volume space velocity 2000 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 80%;

[0069] Among them, the first metal component (zinc + nickel) and the second metal component (molybdenum) are both calculated as oxides, the mass of the first metal component accounts for 80% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 15% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (molybdenum oxide) accounts for 0.5% of the sum of the masses of the carrier and the first metal component.

[0070] Example 2

[0071] (1) 70 g of small-pore pseudo-boehmite, 315 g of large-pore pseudo-boehmite, 115 g of titanium oxide, 10 g of sodium methylcellulose and 470 g of zinc oxide powder were mixed evenly, 450 g of water and 39 g of nitric acid were added, and after mixing evenly, the mixture was extruded into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 18 hours, then dried at 80° C. for 10 hours, and then calcined at 450° C. for 5 hours to obtain a first spherical intermediate;

[0072] (2) Weighing 100 g of nickel acetate tetrahydrate, adding 3400 g of water to prepare a first impregnation solution, placing the first intermediate in the first impregnation solution, and impregnating at 40° C. for 10 h; drying the obtained impregnation product at room temperature for 18 h, then drying at 90° C. for 9 h, and then calcining at 550° C. for 3 h to obtain a second intermediate in the form of a small sphere;

[0073] (3) Weighing 18.9 g of stannous chloride, adding 3400 g of water to prepare a second impregnation solution, placing the second intermediate in the second impregnation solution, and impregnating at 50° C. for 8 h; drying the obtained impregnation product at room temperature for 24 h, then drying at 100° C. for 7 h, and then calcining at 500° C. for 4 h to obtain a spherical catalyst precursor;

[0074] (4) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S2; wherein the reduction treatment conditions are: pressure 0.5 MPa, temperature 350° C., reduction treatment time 4 h, hydrogen volume space velocity 1500 h -1 , the volume fraction of hydrogen in the hydrogen-containing atmosphere is 90%;

[0075] Among them, the first metal component (zinc + nickel) and the second metal component (tin) are both calculated as oxides, the mass of the first metal component accounts for 50% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 3% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (tin oxide) accounts for 1.5% of the sum of the masses of the carrier and the first metal component.

[0076] Example 3

[0077] (1) 65 g of small-pore pseudo-boehmite, 196 g of large-pore pseudo-boehmite, 39 g of titanium oxide, 20 g of sesbania powder and 600 g of zinc oxide powder were mixed evenly, 460 g of water and 52 g of nitric acid were added, and the mixture was evenly mixed and squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 12 hours, then dried at 90° C. for 7 hours, and then calcined at 500° C. for 3 hours to obtain a first spherical intermediate;

[0078] (2) Weighing 389 g of nickel nitrate hexahydrate, adding 1700 g of water to prepare a first impregnation solution, placing the first intermediate in the first impregnation solution, and impregnating at 55° C. for 10 h; drying the obtained impregnation product at room temperature for 20 h, then drying at 100° C. for 8 h, and then calcining at 450° C. for 5 h to obtain a second intermediate in the form of small balls;

[0079] (3) Weighing 13.6 g of ammonium molybdate, adding 2000 g of water to prepare a second impregnation solution, placing the second intermediate in the second impregnation solution, and impregnating at 65° C. for 8 h; drying the obtained impregnation product at room temperature for 18 h, then drying at 80° C. for 10 h, and then calcining at 650° C. for 4 h to obtain a spherical catalyst precursor;

[0080] (4) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S3; wherein the reduction treatment conditions are: pressure 0.75 MPa, temperature 450° C., reduction treatment time 2 h, hydrogen volume space velocity 2500 h -1 , the volume fraction of hydrogen in the hydrogen-containing atmosphere is 70%;

[0081] Among them, the first metal component (zinc + nickel) and the second metal component (molybdenum) are both calculated as oxides, the mass of the first metal component accounts for 70% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 10% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (molybdenum oxide) accounts for 1% of the sum of the masses of the carrier and the first metal component.

[0082] Example 4

[0083] (1) 67 g of small-pore pseudo-boehmite, 266 g of large-pore pseudo-boehmite, 67 g of titanium oxide, 30 g of sodium methylcellulose and 500 g of zinc oxide powder were mixed evenly, 420 g of water and 100 g of nitric acid were added, and after mixing evenly, the mixture was extruded into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 12 hours, then dried at 110° C. for 6 hours, and then calcined at 650° C. for 3 hours to obtain a first spherical intermediate;

[0084] (2) Weigh 333 g of nickel acetate tetrahydrate, add 2000 g of water to prepare a first impregnation solution, place the first intermediate in the first impregnation solution, and impregnate at 55° C. for 11 h; dry the obtained impregnation product at room temperature for 24 h, then dry it at 80° C. for 10 h, and then calcine it at 500° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0085] (3) Weighing 25 g of stannous chloride, adding 2500 g of water to prepare a second impregnation solution, placing the second intermediate in the second impregnation solution, and impregnating at 60° C. for 12 h; drying the obtained impregnation product at room temperature for 36 h, then drying at 80° C. for 8 h, and then calcining at 550° C. for 3 h to obtain a spherical catalyst precursor;

[0086] (4) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S4; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 450° C., reduction treatment time 2 h, hydrogen volume space velocity 3000 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 60%;

[0087] Among them, the first metal component (zinc + nickel) and the second metal component (tin) are both calculated as oxides, the mass of the first metal component accounts for 60% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 10% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (tin oxide) accounts for 2% of the sum of the masses of the carrier and the first metal component.

[0088] Example 5

[0089] (1) 53 g of small-pore pseudo-boehmite, 187 g of large-pore pseudo-boehmite, 60 g of titanium oxide, 45 g of sesbania powder and 650 g of zinc oxide powder were mixed uniformly, 400 g of water and 96 g of nitric acid were added, and after mixing uniformly, the mixture was squeezed into small balls with a particle diameter of 2 mm, and the small balls were naturally dried at room temperature for 20 hours, then dried at 80° C. for 10 hours, and then calcined at 450° C. for 5 hours to obtain a first spherical intermediate;

[0090] (2) Weighing 195 g of nickel nitrate hexahydrate, adding 2800 g of water to prepare a first impregnation solution, placing the first intermediate in the first impregnation solution, and impregnating at 45° C. for 12 h; drying the obtained impregnation product at room temperature for 12 h, then drying at 100° C. for 10 h, and then calcining at 500° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0091] (3) Weighing 12.6 g of stannous chloride, adding 2000 g of water to prepare a second impregnation solution, placing the second intermediate in the second impregnation solution, and impregnating at 100° C. for 8 h; drying the obtained impregnation product at room temperature for 24 h, then drying at 100° C. for 6 h, and then calcining at 650° C. for 3 h to obtain a spherical catalyst precursor;

[0092] (4) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S5; wherein the reduction treatment conditions are: pressure 0.5 MPa, temperature 400°C, reduction treatment time 3 h, hydrogen volume space velocity 2000 h-1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 80%;

[0093] Among them, the first metal component (zinc + nickel) and the second metal component (tin) are both calculated as oxides, the mass of the first metal component accounts for 70% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 5% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (tin oxide) accounts for 1% of the sum of the masses of the carrier and the first metal component.

[0094] Example 6

[0095] (1) 74 g of small-pore pseudo-boehmite, 259 g of large-pore pseudo-boehmite, 67 g of titanium oxide, 30 g of sodium carboxymethyl cellulose and 520 g of zinc oxide powder were mixed uniformly, 390 g of water and 100 g of nitric acid were added, and the mixture was uniformly mixed and extruded into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 48 hours, then dried at 90° C. for 8 hours, and then calcined at 450° C. for 5 hours to obtain a first spherical intermediate;

[0096] (2) Weighing 266 g of nickel acetate tetrahydrate, adding 1700 g of water to prepare a first impregnation solution, placing the first intermediate in the first impregnation solution, and impregnating at 55° C. for 11 h; drying the obtained impregnation product at room temperature for 24 h, then drying at 110° C. for 6 h, and then calcining at 650° C. for 3 h to obtain a second intermediate in the form of a small sphere;

[0097] (3) Weighing 20.4 g of ammonium molybdate, adding 1000 g of water to prepare a second impregnation solution, placing the second intermediate in the second impregnation solution, and impregnating at 65° C. for 6 h; drying the obtained impregnation product at room temperature for 18 h, then drying at 110° C. for 7 h, and then calcining at 500° C. for 5 h to obtain a spherical catalyst precursor;

[0098] (4) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S6; wherein the reduction treatment conditions are: pressure 1 MPa, temperature 350° C., reduction treatment time 3 h, hydrogen volume space velocity 2500 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 100%;

[0099] Among them, the first metal component (zinc + nickel) and the second metal component (molybdenum) are both calculated as oxides, the mass of the first metal component accounts for 60% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 8% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (molybdenum oxide) accounts for 1.5% of the sum of the masses of the carrier and the first metal component.

[0100] Comparative Example 1 to Comparative Example 6

[0101] The difference between Comparative Example 1 and Example 3 is that the small-pore pseudo-boehmite in step (1) is replaced by large-pore pseudo-boehmite to obtain the adsorption desulfurization catalyst D1.

[0102] The difference between Comparative Example 2 and Example 3 is that the macroporous pseudo-boehmite in step (1) is replaced by microporous pseudo-boehmite to obtain the adsorption desulfurization catalyst D2.

[0103] The difference between Comparative Example 3 and Example 3 is that the titanium oxide in step (1) is replaced by macroporous pseudo-boehmite to obtain an adsorptive desulfurization catalyst D3.

[0104] The difference between Comparative Example 4 and Example 4 is that the titanium oxide in step (1) is replaced by macroporous pseudo-boehmite to obtain an adsorption desulfurization catalyst D4.

[0105] The difference between Comparative Example 5 and Example 5 is that the nickel component is not impregnated, that is, step (2) is eliminated, and the first intermediate obtained in step (1) is directly subjected to steps (3) and (4) in sequence, and the remaining conditions are the same as those in Example 5, to obtain adsorption desulfurization catalyst D5.

[0106] The difference between Comparative Example 6 and Example 6 is that the second metal component is not impregnated, that is, step (3) is cancelled, and the second intermediate obtained in step (2) is directly used as a catalyst precursor for reduction treatment in step (4). The remaining conditions are the same as those in Example 6 to obtain adsorption desulfurization catalyst D6.

[0107] Application Examples

[0108] The desulfurization process of this application example is as follows: 200g of catalyst is loaded into a fixed bed reactor, and then a heavy oil raw material is introduced into the fixed bed reactor, and is contacted and reacted with the adsorption desulfurization catalyst under a hydrogen atmosphere (i.e., a desulfurization reaction is performed), and a desulfurized oil product and a catalyst to be regenerated are obtained respectively; wherein the heavy oil raw material is a vacuum residue oil with a sulfur content of 1.7wt%, and the conditions of the desulfurization process are: a temperature of 420°C, a pressure of 4MPa, a feed rate of 100g / h of the heavy oil raw material (the feed space velocity of the heavy oil raw material is 0.5h -1 ), hydrogen flow rate 35L / h (the volume ratio of hydrogen to heavy oil feedstock is 400:1).

[0109] S1-S6 and D1-D6 were used as adsorption desulfurization catalysts to carry out the above desulfurization process, so as to evaluate the performance of S1-S6 and D1-D6. The crushing strength of catalysts S1-S6 and D1-D6 and the desulfurization rate achieved by each catalyst are shown in Table 1 and Table 2 respectively.

[0110] Table 1 Performance evaluation results of adsorption desulfurization catalyst

[0111] Adsorption desulfurization catalyst S1 S2 S3 S4 S5 S6 Crushing strength / N 30 34 35 33 36 37 Desulfurization rate / % 78 75 78 77 79 76

[0112] Table 2 Performance evaluation results of adsorption desulfurization catalyst

[0113] Adsorption desulfurization catalyst D1 D2 D3 D4 D5 D6 Crushing strength / N 12 21 31 28 33 34 Desulfurization rate / % 79 45 72 70 25 35

[0114] It can be seen from Table 1 and Table 2 that, compared with D1-D6, S1-S6 have both good mechanical properties and desulfurization activity.

[0115] In addition, the catalyst stability of S1~S6 and D1~D6 was evaluated, and the desulfurization activity of the catalyst after different regeneration times was measured. The results showed that the desulfurization activity stability of S1~S6 was much better than that of D1~D6. Specifically, the desulfurization rate of the catalyst after different regeneration times was measured according to the following desulfurization-regeneration process:

[0116] The above desulfurization process is carried out using unused fresh catalyst to obtain desulfurized oil products and once-regenerated catalyst, and the desulfurization rate of the fresh catalyst is measured;

[0117] The regenerated catalyst is regenerated according to the following regeneration process: the regenerated catalyst is oxidized and regenerated in the presence of an oxygen-containing gas to obtain a regenerated catalyst precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 7%, and the volume space velocity of the oxygen-containing gas is 2000h -1 The temperature of the oxidation regeneration is 350°C, the pressure of the oxidation regeneration is 0.5 MPa, and the time of the oxidation regeneration is 60 h; the regenerated catalyst precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain a regenerated catalyst (i.e., regenerated once); wherein the volume fraction of hydrogen in the atmosphere containing hydrogen is 75%, and the volume space velocity of hydrogen is 2000 h -1 , the temperature of the second reduction treatment is 400°C, the pressure of the second reduction treatment is 1.0MPa, and the time of the second reduction treatment is 4h;

[0118] The above desulfurization process is carried out using a once-regenerated catalyst to obtain a desulfurized oil product and a second-time regenerated catalyst, and the desulfurization rate of the once-regenerated catalyst is measured; the second-time regenerated catalyst is then regenerated according to the above regeneration process to obtain a second-time regenerated catalyst (i.e., regenerated twice); the above desulfurization process is carried out using a second-time regenerated catalyst to obtain a desulfurized oil product and a second-time regenerated catalyst, and the desulfurization rate of the second-time regenerated catalyst is measured… According to the above process, the desulfurization rates after the catalyst is regenerated 1, 4, 7, 10, 13, 16, 19, 22, 25, 28, 32, and 35 times are measured respectively.

[0119] Taking S3, S4, D3 and D4 as examples, the desulfurization rates corresponding to different regeneration times measured according to the above process are shown in Table 3.

[0120] Table 3 Catalyst stability evaluation results

[0121]

[0122] Note: After D3 and D4 were regenerated 13 times, the desulfurization rate dropped significantly and is not shown in Table 3.

[0123] It can be seen from Table 3 that after S3 and S4 were regenerated 35 times, they were still able to maintain a high desulfurization rate, which was basically equivalent to that of the fresh adsorption desulfurization catalyst, showing good desulfurization activity stability; in addition, the crushing strengths of S3 and S4 after 35 regenerations were measured to be 33N and 31N respectively, and they also showed good structural stability and other properties.

[0124] In addition, in order to further illustrate the performance difference between the adsorption desulfurization catalyst prepared in the embodiment and the adsorption desulfurization catalyst prepared in the comparative example, taking S1, S2, D3, and D4 as examples, the catalyst precursor in the preparation process (i.e., the product before the first reduction treatment) and the regenerated catalyst precursor when the fifth regeneration is carried out according to the above desulfurization-regeneration process (i.e., the product before the second reduction treatment) are subjected to XRD analysis, and the results are shown in FIG. Figure 1 and Figure 2 ,in, Figure 1 The fresh agent S1 is a catalyst precursor in the preparation process of the fresh adsorption desulfurization catalyst S1, the fresh agent S2 is a catalyst precursor in the preparation process of the fresh adsorption desulfurization catalyst S2, the fresh agent D3 is a catalyst precursor in the preparation process of the fresh adsorption desulfurization catalyst D3, and the fresh agent D4 is a catalyst precursor in the preparation process of the fresh adsorption desulfurization catalyst D4; Figure 2 The regeneration agent S1 is a regeneration catalyst precursor when the fresh adsorption desulfurization catalyst S1 is regenerated for the fifth time according to the above desulfurization-regeneration process, the regeneration agent S2 is a regeneration catalyst precursor when the fresh adsorption desulfurization catalyst S2 is regenerated for the fifth time according to the above desulfurization-regeneration process, the regeneration agent D3 is a regeneration catalyst precursor when the fresh adsorption desulfurization catalyst D3 is regenerated for the fifth time according to the above desulfurization-regeneration process, and the regeneration agent D4 is a regeneration catalyst precursor when the fresh adsorption desulfurization catalyst D4 is regenerated for the fifth time according to the above desulfurization-regeneration process.

[0125] from Figure 1 and Figure 2It can be seen that the main characteristic diffraction peaks in fresh agent S1, fresh agent S2, fresh agent D3 and fresh agent D4 are zinc oxide crystal phase peaks (2θ is 31.5°, 34.4° and 36.2°) and nickel oxide crystal phase peaks (2θ is 36.9° and 43.0°). The characteristic diffraction peak of ZnO is sharp and has high intensity, and it is the main active component. Compared with the fresh agent, the XRD spectra of the regenerated agent (i.e., regenerated agent S1, regenerated agent S2, regenerated agent D3 and regenerated agent D4) are Figure 2 ) is significantly more complex, in which, in addition to regeneration products such as ZnO and NiO, new phases such as desulfurization products ZnS and ZnAl2O4 are generated. Compared with regeneration agents S1, S2, D3 and D4, the intensity of the characteristic diffraction peak of zinc-aluminum spinel is significantly enhanced in the XRD spectra.

[0126] The active ZnO in the adsorption desulfurization catalyst continuously reacts with the aluminum source in the carrier to generate inactive zinc-aluminum spinel, and the zinc-aluminum spinel can no longer be converted into active ZnO during the regeneration process, indicating that it is difficult to regenerate, thereby forming an inactive component, and due to its high content, it will cause the content of the active component ZnO in the adsorption desulfurization catalyst to be greatly reduced, thereby causing problems such as difficulty in sulfur transfer during the adsorption desulfurization process, affecting the desulfurization activity and other properties of the adsorption desulfurization catalyst; at the same time, the formation of zinc-aluminum spinel will also destroy the carrier structure, resulting in a decrease in the strength of the adsorption desulfurization catalyst, making the adsorption desulfurization catalyst more easily broken and deteriorating in performance. Therefore, the above XRD analysis further illustrates that, relative to the adsorption desulfurization catalyst prepared in the comparative example, the adsorption desulfurization catalyst prepared in the embodiment has better desulfurization activity stability and mechanical strength and other properties.

[0127] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An adsorption desulfurization catalyst, characterized in that: The invention comprises a carrier, a first metal component and a second metal component, wherein the first metal component comprises zinc oxide and nickel, the second metal component comprises molybdenum oxide and / or tin oxide, and the carrier is compounded by raw materials comprising macroporous pseudo-boehmite, microporous pseudo-boehmite and titanium oxide, wherein the microporous pseudo-boehmite has a pore volume of 0.4 mL / g to 0.8 mL / g and a specific surface area of ​​180 m 2 / g~260m 2 / g; the pore volume of the macroporous pseudo-boehmite is 0.8mL / g~1.2mL / g, and the specific surface area is 260 m 2 / g~360m 2 / g; the mass ratio of the small-pore pseudo-boehmite to the large-pore pseudo-boehmite is 1: (2.5-4.5); Calculated based on the oxide of the first metal component and the oxide of the second metal component, the following conditions are satisfied: The mass of the first metal component accounts for 50% to 80% of the sum of the mass of the carrier and the first metal component; and / or, The mass of the nickel compound in the first metal component accounts for 3% to 15% of the sum of the mass of the carrier and the first metal component; and / or, The mass of the second metal component accounts for 0.5% to 2% of the sum of the mass of the carrier and the first metal component.

2. The adsorption desulfurization catalyst according to claim 1, characterized in that: The peptization index of the small-pore pseudo-boehmite is greater than 95%; and / or, The ratio of the mass of the titanium oxide to the sum of the mass of the macroporous pseudo-boehmite and the microporous pseudo-boehmite is (0.1-0.3):

1.

3. The method for preparing the adsorptive desulfurization catalyst according to any one of claims 1 to 2, characterized in that: include: (I) adding an inorganic acid and water to a mixture containing macroporous pseudo-boehmite, microporous pseudo-boehmite, titanium oxide, a binder, and zinc oxide, and then sequentially performing molding, drying, and calcining to obtain a first intermediate; (II) impregnating the first intermediate with a first impregnation solution containing a nickel compound, and drying and calcining the impregnation product to obtain a second intermediate; (III) impregnating the second intermediate with a second impregnation solution containing a compound of a second metal component, and drying and calcining the impregnation product to obtain a catalyst precursor; (IV) subjecting the catalyst precursor to a first reduction treatment in an atmosphere containing hydrogen to obtain the adsorptive desulfurization catalyst.

4. The preparation method according to claim 3, characterized in that: The zinc oxide comprises nano zinc oxide powder having a particle size not greater than 100 nm; and / or, The binder comprises at least one of sodium methyl cellulose, sodium carboxymethyl starch, sodium carboxymethyl cellulose and sesbania powder; and / or, The nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 1% to 5% of the sum of the mass of the macroporous pseudo-boehmite, microporous pseudo-boehmite, titanium oxide, zinc oxide and the nickel compound; and / or, The ratio of the mass of the inorganic acid to the sum of the mass of the macroporous pseudo-boehmite and the microporous pseudo-boehmite is (0.1-0.5):

1.

5. The preparation method according to claim 3 or 4, characterized in that: The calcination conditions in step (I) are: calcination temperature of 400° C. to 700° C., calcination time of 1 h to 10 h; and / or, The calcination conditions in step (II) are: calcination temperature of 400°C to 700°C, calcination time of 1h to 10h; and / or, The calcination conditions in step (III) are: calcination temperature of 400°C to 700°C, calcination time of 1h to 10h; and / or, In step (IV), the volume space velocity of hydrogen is 500h -1 ~4000h -1 The temperature of the first reduction treatment process is 300°C to 500°C, the pressure of the first reduction treatment process is 0 to 3MPa, and the time of the first reduction treatment is 1h to 6h.

6. A method for desulfurization of sulfur-containing oil by adsorption, characterized in that: include: Desulfurization of sulfur-containing oil products using the adsorption desulfurization catalyst according to any one of claims 1 to 2; or, The adsorption desulfurization catalyst is prepared according to the preparation method described in any one of claims 3 to 5, and the prepared adsorption desulfurization catalyst is used to desulfurize sulfur-containing oil products.

7. The method for desulfurization of sulfur-containing oil by adsorption according to claim 6, characterized in that: The temperature of the desulfurization treatment is 300°C to 550°C; and / or, The desulfurization treatment pressure is 0.5MPa to 10MPa; and / or, The feed space velocity of the sulfur-containing oil is 0.1h -1 ~1.0h -1 and / or, The desulfurization treatment is carried out in a hydrogen atmosphere, and the volume ratio of the hydrogen to the sulfur-containing oil is (100-800):

1.

8. The method for desulfurization of sulfur-containing oil by adsorption according to claim 6, characterized in that: Also includes: After the desulfurization treatment, a desulfurized oil product and a catalyst to be regenerated are obtained respectively; subjecting the catalyst to be regenerated to a regenerated catalyst; The regenerated catalyst is returned to the desulfurization process; wherein the regeneration process comprises: The regenerated catalyst is oxidized and regenerated in the presence of an oxygen-containing gas to obtain a regenerated catalyst precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, and the volume space velocity of the oxygen-containing gas is 1000h -1 ~3000h -1 , the temperature of the oxidation regeneration is 300°C to 500°C, the pressure of the oxidation regeneration is 0 to 0.5MPa, and the time of the oxidation regeneration is 20h to 100h; The regenerated catalyst precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain the regenerated catalyst; wherein the volume space velocity of the hydrogen is 500h -1 ~4000h -1 The temperature of the second reduction treatment is 300°C to 500°C, the pressure of the second reduction treatment is 0 to 3 MPa, and the time of the second reduction treatment is 1h to 6h.

9. The method for desulfurization of sulfur-containing oil by adsorption according to claim 6, characterized in that: The sulfur component in the sulfur-containing oil product includes at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, and the thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene; and / or, the sulfur-containing oil product includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

Citation Information

Patent Citations

  • Combined aluminum oxide-based selective hydrodesulfurization catalyst and preparation method thereof

    CN101439288A

  • Adsorptive desulfurization adsorbent and preparation method thereof

    CN102463099A

  • Adsorbent composition for desulfuration of hydrocarbon oil and preparation method thereof

    CN103372416A

  • High-selectivity gasoline adsorption desulfurizer as well as preparation method and application thereof

    CN104028217A

  • Fuel oil deep-adsorption desulfurizationn catalyst, preparation method and application thereof

    CN104056632A